FIELD RESEARCH ON RETROFIT BUCKING BAR NOISE OF BAR MACHINES - Victor A. Finochenko; Igor V. Boguslavskiy (Advanced Engineering Research, 2012)
The bar machines with retrofit bucking bar noise - level measurements are resulted. It is shown that con siderable noise abatement has caused satisfaction of the sanitary norm requirements for the equipment.